Pengaruh Model Pembelajaran Three Stheep Interview dengan Strategi Concept Learning terhadap pemahaman konsep siswa - Lia Ermawati; Imas Cintamulya (Universitas Sebelas Maret, 2018)
Three Stheep Interview learning model is a model of cooperative learning where students are required to be able to group, communicate with friends, and can be more active in the learning process, besides by combining learning strategies Concept Learning, then students can be able to create a concept or own understanding of the material which is taught by the teacher. From this statement, the purpose of this research is to know the influence of learning model of Three Stheep Interview with Concept Learning strategy to understanding student concept. This research type is quasi experiment research that is in experiment class using learning model of three stheep interview and control class is not given learning model or only conventional learning. The data obtained from the test score about the concept of student understanding in the analysis using t-test that is with a sample of 31 students in the experimental class and 31 students in the control class. The ability to understand students' concepts in this case includes re-enacting a concept and applying concepts. The difference of students' concept comprehension level from the t-test shows that the mean value of post test of the experimental class is 82,4839 while the mean of post test class test value is 75,7742, with significance level equal to 0,013 (P = <0,05 ). Then it can be concluded that the learning model of Three Stheep Interview and Concept Learning strategy can improve students' concept understanding.